The Nalakīrtikaumudī of Agastyapaṇḍita - Agastyapaṇḍita, 14th cent (D. K. Pub. House, 1975)
Extant portion of a poem recounting the legendary story of Nala and Damayanti; transcribed from a single manuscript preserved in the India Office Library, London.